Experimental model of proliferative vitreoretinopathy (PVR) in the vitrectomised eye: effect of silicone oil. - Lean, J S (Br J Ophthalmol, 1984)
Silicone oil alone or as an adjunct to vitrectomy is widely used for the treatment of retinal detachment complicated by proliferative vitreoretinopathy (PVR). It appears to reduce the tendency for recurrent traction detachment, but the mechanism of this action is obscure. We have studied the effects of silicone oil in an experimental animal model. Twenty five thousand homologous fibroblasts were injected into the aphakic vitrectomised rabbit eye, and traction detachment of the vascularised retina (medullary rays) regularly resulted. Intraocular silicone oil did not influence the development of this experimental detachment. IMAGES: